Field notes contributed by Stephen J. Dinsmore, spring 1988 - Dinsmore, Stephen J.et al (1988)
List of birds and locations contributed by Stephen J. Dinsmore with detailed descriptions. The field notes include bird sightings from several observers. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1988. Epson - sheet feed